Galectin-3 as a possible link between periodontitis and chronic kidney disease: a cross-sectional study - Sri Vidhya Marimuthu; Devi Arul; Muthukumar Santhanakrishnan; Ramprasad Elumalai; Sandhya Suresh; Sathya Selvarajan; Ravindranath Dhulipalla; Ramanarayana Boyapati (Journal of Yeungnam Medical Science)
Background Chronic periodontitis is associated with various systemic inflammatory diseases; however, research on its association with chronic kidney disease (CKD) is relatively limited. Because both conditions share common risk factors, systemic inflammation plays a key role in the progression of these diseases. Galectin-3 (Gal-3) is a proinflammatory cytokine that plays an important role in chronic inflammatory diseases and is a potential biomarker. This study aimed to measure salivary Gal-3 levels in patients with periodontitis and CKD to better understand their association and evaluate Gal-3 as a diagnostic biomarker for these conditions. Methods Seventy-five patients were categorized into three groups: Group I, patients with CKD and periodontitis (n=25); Group II, patients with chronic periodontitis who were systemically healthy (n=25); and Group III, patients with CKD without chronic periodontitis (n=25). Demographic characteristics and periodontal and renal parameters were recorded for each patient. Saliva samples were collected to evaluate Gal-3 levels using an enzyme-linked immunosorbent assay. Results Patients with chronic periodontitis and CKD and those with chronic periodontitis alone (Groups I and II, respectively) showed significantly higher salivary Gal-3 levels than patients with CKD alone (Group III) (p<0.001). Bivariate correlation analysis indicated a strong relationship between clinical parameters and Gal-3 levels across all three groups. Conclusion Salivary Gal-3 level is a valuable early diagnostic marker of chronic periodontitis and CKD.